PEMIKIRAN K.H. HASYIM ASY'ARI TENTANG PENDIDIKAN ISLAM DAN RELEVANSINYA DALAM PENDIDIKAN ISLAM KONTEMPORER - Amir Mukminin; Dedi Rismanto; Maragustam Siregar; Maulana Iskandar (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2022)
This study aims to find out K.H Hasyim Asy'ari's thoughts about Islamic education, and whether they are still relevant in Islamic education in contemporary times. Education is also like health, including basic needs that must be fulfilled in every human being. Education is a cultural process that elevates human dignity throughout life. Education plays a decisive role in human existence and development. Therefore, it is necessary to have motivation in efforts to explore potential, direction (orientation) and good planning in the development of contemporary education. The method used in this research is qualitative research using a type of bibliography research or often interpreted as Library Research. This research analyzes content or what is often called content analysis. This content analysis is used to compare one research with other research in accordance with this article. The results of the discussion K.H. Hasyim Asy'ari did not explicitly explain the concept of his educational goals. However, it can be implicitly read from some of his statements. K.H.'s ideal goal Hasyim Asy'ari is to form a highly ethical society (akhlaq al karimah). The purpose of education is, First, to form a perfect human being who aims to get closer to Allah SWT, Second is to form a perfect human being who gets the happiness of the world and the hereafter. Keywords: Biography of KH Hasyim Asy'ari, Islamic Education, Contemporary